Alterations in blood pressure, antioxidant status and caspase 8 expression in cobalt chloride-induced cardio-renal dysfunction are reversed by Ocimum gratissimum and gallic acid in Wistar rats (2016)
The protective abilities of the chloroform extract of Ocimum gratissimum (COG) and gallic acid against cobalt chloride (CoCl2) − induced cardiac and renal toxicity were evaluated. Rats were exposed to CoCl2 (350 ppm) for 7 days, either alone, or in combination with COG (100 and 200 mg/kg) or gallic acid (120 mg/kg). CoCl2 given alone, caused significant increases (p < 0.05) in oxidative stress parameters (hydrogen peroxide, H2O2 and malondialdehyde, MDA) and increased expression of the apoptotic initiator caspase 8 in the heart and kidneys. There was significant reduction (p < 0.05) in reduced glutathione (GSH) in cardiac and renal tissues; reduction in superoxide dismutase (SOD) activity in the kidneys and adaptive increases in Glutathione S-transferase (GST) and catalase (CAT). CoCl2 also produced significant reduction (p < 0.05) in systolic (SBP), diastolic (DBP) and mean arterial (MAP) blood pressures. Oral COG and gallic acid treatment significantly reduced (p < 0.05) the levels of H2O2 and MDA; with reduced expression of caspase 8 and restoration of GSH levels, GPx, SOD and CAT activities, howbeit, to varying degrees in the heart and kidneys. COG (200 mg/kg) was most effective in restoring the blood pressures in the rats to near control levels. CoCl2-induced histopathological lesions including myocardial infarction and inflammation and renaltubular necrosis and inflammation were effectively ameliorated by the treatments administered. This study provides evidence for the protective roles of O. gratissimum and gallic acid by modulation of CoCl2-induced alterations in blood pressure, antioxidant status and pro-apoptotic caspase 8 in Wistar rats.